Ultra-high speed optical network - Cheng, Tee Hiang (2008)
Wavelength Division Multiplexing (WDM) is a promising technique for utilizing the bandwidth of the optical fiber. The design of limited-wavelength-interchanging cross-connects (L-WIXC) is considered in this thesis and their performance is studied from several aspects.